Evaluasi Jalan Ambulu-Watu Ulo menggunakan Metode International Road Assessment Programme (IRAP) - Firdausy, Muhammad Thoriqul (Fakultas Teknik, 2026)
High enthusiasm among both local and non-local tourists has led to increased traffic volume on the roads leading to Jember's south coast attractions—particularly the Watu Ulo route—thereby raising the risk of accidents. Road safety issues impact the economy and state finances, necessitating special attention to traffic accident prevention. This study aims to assess existing road safety levels and identify measures to improve safety on the Ambulu-Watu Ulo road using the International Road Assessment Programme (iRAP) framework. A case study methodology was employed, with the scope defined by specific timeframes and activities. The initial star rating assessment for the Ambulu-Watu Ulo road under existing conditions yielded an overall 3-star rating, indicating a fair level of safety and low risk. For vehicle occupants, 97 segments received a 3-star rating, and 8 segments received a 4-star rating. For motorcycles, the results showed 6 segments with 4 stars, 94 segments with 3 stars, and 5 segments with 2 stars. For bicyclists, 51 segments were rated 3 stars, 48 segments 2 stars, and 6 segments 1 star. For pedestrians, 7 segments received a 3-star rating, 52 segments received 2 stars, and 46 segments received 1 star. The most optimal treatment methods for the Ambulu-Watu Ulo road—determined through a trial-and-error approach—include the installation of speed limit signs, shoulder rumble strips, speed bumps, and pedestrian crossing signs.
Validasi dan Finalisasi Repositori File 02 Juli 2026_Kholif Basri
Keywords: accident; road safety; IRAP methodology; star rating; Watu Ulo